Changes in Local Atrial Electrograms and Surface ECG Induced by Acute Atrial Myocardial Infarction - Amorós-Figueras, Gerard; Roselló-Diez, Elena; Sanchez-Quintana, Damian; Casabella-Ramon, Sergi; Jorge, Esther; Nevado-Medina, Jorge; Arzamendi, Dabit; Millán, Xavier; Alonso-Martin, Concepción; Guerra, Jose M.; Cinca, Juan (Frontiers in Physiology, 2020)
Background: Atrial coronary branch occlusion is a hardly recognizable clinical entity that can promote atrial fibrillation. The low diagnostic accuracy of the ECG could deal with the characteristics of the ischemia-induced changes in local atrial electrograms, but these have not been described. Objectives: We analyzed the effects of selective acute atrial branch occlusion on local myocardial structure, atrial electrograms, and surface ECG in an experimental model close to human cardiac anatomy and electrophysiology. Methods: Six anesthetized open-chest anaesthetized pigs underwent surgical occlusion of an atrial coronary branch arising from the right coronary artery during 4 hours. Atrial electrograms and ECG were simultaneously recorded. One additional pig acted as sham control. In all cases, the hearts were processed for anatomopathological analysis. Results: Atrial branch occlusion induced patchy atrial necrosis with sharp border zone. During the first 30min of occlusion, atrial electrograms showed progressive R-wave enlargement (1.8±0.6mV vs. 2.5±1.1mV, p<0.01), delayed local activation times (28.5±8.9ms vs. 36.1±16.4ms, p<0.01), ST-segment elevation (-0.3±0.3mV vs. 1.0±1.0mV, p<0.01), and presence of monophasic potentials. Atrial ST-segment elevation decreased after 2h of occlusion. The electrical border zone was about 1mm and expanded over time. After 2h of occlusion the ECG showed a decrease in P-wave amplitude (from 0.09±0.04mV to 0.05±0.04mV after 165 min occlusion, p<0.05) and duration (64.4±8.0ms vs. 80.9±12.6ms, p<0.01). Conclusions: Selective atrial branch occlusion induces patchy atrial infarction and characteristic changes in atrial activation, R/S-wave, and ST-segment that are not discernible at the ECG. Only indirect changes in P-wave amplitude and duration were appreciated in advanced stages of acute coronary occlusion.